Pancasila and the Challenge of Morality: A Response to the LGBT Phenomenon in Higher Education Environments - Hudi, Ilham; Matang; Lisman, Muhammad (Department of Pancasila and Civic Education, Universitas Negeri Medan, 2025)
LGBT phenomena in the campus environment are not in line with the values of Pancasila as a nation's moral guideline and cause various debates in society. This study explores how Pancasila can be used as a basis for responding to LGBT phenomena in the campus environment. With a qualitative approach and phenomenological method, this research collects data through in-depth interviews with students and observations on campus. The results showed that the values of Pancasila applied by students in responding to LGBT phenomena by not supporting their existence in the campus environment. Students conduct socialization activities that reject LGBT, hold discussions on their negative impacts, embrace their friends who have fallen into the moral values of Pancasila, and engage in various activities aimed at maintaining social and moral norms that are in line with the values of Pancasila. Based on research findings, policy regulations are needed that become guidelines for the campus in addressing the LGBT phenomenon.